The Analysis of Parental Interest in Islamic and Non-Islamic Schools at Elementary School Level in Rural Areas, Wonosobo, Central Java, Indonesia - Cahyani, Ida; Sahid, Sahid; Widiyantoro, Arif (ANTHOR: Education and Learning Journal, 2026)
This study aims to analyze parental interest and motivation in choosing Islamic and non-Islamic elementary schools in rural areas of Wonosobo, Central Java. The background of this research is based on the increasing variety of educational institutions, which creates complex considerations for parents in selecting appropriate schools for their children. This study employed a qualitative descriptive method. Data were collected through observation, questionnaires, and documentation from 83 parent respondents from SDN 1 Ngadikerso and MI Ma’arif Bendosari. The data were analyzed using data reduction, data display, and conclusion drawing, supported by triangulation techniques to ensure validity. The findings reveal that the primary factors influencing parents’ choices are the completeness of learning facilities (60.24%) and the proximity of the school (20.48%). Additionally, Islamic religious education plays a significant role, particularly in Islamic schools, as parents expect these institutions to develop their children's character, morality, and religious understanding. Meanwhile, non-Islamic schools are preferred for their contribution to students’ cognitive development, literacy skills, and broader scientific knowledge. In conclusion, parental decision-making is influenced by a combination of pragmatic factors and value-based expectations, particularly regarding religious character formation and the quality of education provided by schools.